The Influence of Human Resources Audit and Internal Control System on Employee Performance in PT. Subur Sedaya Maju Prabumulih - Praja, Rico Adrian; Mardiana, Tri; Pratiwi, Krisnandini Wahyu (Journal of Business Innovation and Research, 2023)
This study aims to analyze the Effect of the Human Resources Audit and Internal Control System on Employee Performance at PT. Subur Sedaya Maju In Prabumulih". This research design is descriptive and quantitative research using the census method or total sampling, namely a study conducted using samples using the entire population where the population is less than 100 people. Data collection was carried out from April to August 2022. The research population was all employees of PT. Subur Sedaya Maju Prabumulih. Respondents used were 90. Primary data collection techniques were carried out by distributing google form questionnaires. This study uses the IBM SPSS 25 version of the analysis tool. The results of this study indicate that 1) Human Resources Audit and Internal Control System have a positive and significant effect on Employee Performance, 2) Human Resources Audit and Internal Control System partially have a positive and significant effect on Employee Performance, 3) Internal Control System has a dominant influence on Employee Performance the value of the coefficient of determination (Adjusted R2) is 0.471 or 47.1%, this shows that the influence of the Human Resources Audit variable (X1) and Internal Control System (X2) on Employee Performance (Y), is 47.1% and the remaining 52 ,9% influenced by other variables outside the study.